Suspended animation inducer hydrogen sulfide is protective in an in vivo model of ventilator-induced lung injury - Aslami, Hamid (Springer-Verlag, 2010)
PURPOSE: Acute lung injury is characterized by an exaggerated inflammatory response and a high metabolic demand. Mechanical ventilation can contribute to lung injury, resulting in ventilator-induced lung injury (VILI). A suspended-animation-like state induced by hydrogen sulfide (H(2)S) protects against hypoxia-induced organ injury. We hypothesized that suspended animation is protective in VILI by reducing metabolism and thereby CO(2) production, allowing for a lower respiratory rate while maintaining adequate gas exchange. Alternatively, H(2)S may reduce inflammation in VILI. METHODS: In mechanically ventilated rats, VILI was created by application of 25 cmH(2)O positive inspiratory pressure (PIP) and zero positive end-expiratory pressure (PEEP). Controls were lung-protective mechanically ventilated (13 cmH(2)O PIP, 5 cmH(2)O PEEP). H(2)S donor NaHS was infused continuously; controls received saline. In separate control groups, hypothermia was induced to reproduce the H(2)S-induced fall in temperature. In VILI groups, respiratory rate was adjusted to maintain normo-pH. RESULTS: NaHS dose-dependently and reversibly reduced body temperature, heart rate, and exhaled amount of CO(2). In VILI, NaHS reduced markers of pulmonary inflammation and improved oxygenation, an effect which was not observed after induction of deep hypothermia that paralleled the NaHS-induced fall in temperature. Both NaHS and hypothermia allowed for lower respiratory rates while maintaining gas exchange. CONCLUSIONS: NaHS reversibly induced a hypometabolic state in anesthetized rats and protected from VILI by reducing pulmonary inflammation, an effect that was in part independent of body temperature. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00134-010-2022-2) contains supplementary material, which is available to authorized users.